Time, intersubjectivity, and musical relationship in Alfred Schutz - Venturini, Riccardo (SocietàMutamentoPolitica, 2016)
In this work I tackle certain aspects of the relationship between time and intersubjectivity in Alfred Schutz. I present a summary of the methodological architecture of the Austrian sociologist, outlining the specificity of the relationship between time and consciousness. I discuss the treatment of the musical experience as an example of the peculiar declination of a series of temporal dynamics connected to the intersubjective creation of meanings. Finally, I set out some thoughts related to the debate on the relationship between time, intersubjectivity and music in Schutz. The musical relationship is a context endowed with meaning, not the object of conceptualization, that allows us to identify in a paradigmatic way the relationship between the subjective sense and experience of the other. The theory of appresentation of Schutz is the center of the process of constitution of meaning of the understanding of the other. The emergence of meaning is related to the dynamics of the passive and active poles of the consciousness and the constitution, in the we-relation, of a radically intersubjective dimension that exceeds the Cartesian distinction between inside and outside.